2012
DOI: 10.1007/s10479-012-1165-7
|View full text |Cite
|
Sign up to set email alerts
|

A new method for mean-variance portfolio optimization with cardinality constraints

Abstract: Several portfolio selection models take into account practical limitations on the number of assets to include and on their weights in the portfolio. We present here a study of the Limited Asset Markowitz (LAM) model, where the assets are limited with the introduction of quantity and cardinality constraints.\ud We propose a completely new approach for solving the LAM model based on a reformulation as a Standard Quadratic Program, on a new lower bound that we establish, and on other recent theoretical and comput… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
117
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 115 publications
(124 citation statements)
references
References 35 publications
2
117
0
Order By: Relevance
“…Several authors (see, e.g., [44,49,97,133]) require x to be a semi-continuous variable [234], i.e., they require x j ∈ [x j , x j ] ∪ {0} for all j = 1, . .…”
Section: Buy-in Thresholdsmentioning
confidence: 99%
See 2 more Smart Citations
“…Several authors (see, e.g., [44,49,97,133]) require x to be a semi-continuous variable [234], i.e., they require x j ∈ [x j , x j ] ∪ {0} for all j = 1, . .…”
Section: Buy-in Thresholdsmentioning
confidence: 99%
“…Using the theoretical results in [224,236] and extending [45,46,47], Cesarone et al [44] have shown that the problem (3.1) with cardinality constraints (3.16) has the same optimal solution of problem (3.1) with equality cardinality constraints (3.17) and reduce this kind of programs to Standard Quadratic Programming Problem (see [23,24]), avoiding to explicitly introduce binary variables and considering an exact tailored solving procedure, called Increasing Set Algorithm. The Standard Quadratic Programming Problem is an NP-hard problem when the Hessian matrix of the objective function is indefinite, i.e., if the Hessian matrix of the objective function is neither positive nor negative semidefinite [23].…”
Section: Cardinality Constraintsmentioning
confidence: 99%
See 1 more Smart Citation
“…For solving the problem, these authors propose a PSO algorithm. Cesarone et al [2013] analyze a cardinality-constrained version of the POSP. The authors develop an exact algorithm for solving small size instances of the problem.…”
Section: Portfolio Optimization and Selection Problemmentioning
confidence: 99%
“…At a first glance, one could see the problem as a triobjective optimization problem by minimizing the variance of the return, maximizing the expected return, and minimizing the cardinality over the set of feasible portfolios. Such a framework was taken in account in the studies [1,2,10,18]. However, these authors did not investigate the effects of cardinality constraints on portfolio models in terms of out-of-sample performance, a subject still poorly analyzed in the literature.…”
Section: The Cardinality/mean-variance Biobjective Modelmentioning
confidence: 99%